Regional Language Traces in the Use of Indonesian: A Case Study of Student Linguistic Interaction - Asrining Mei Christin Halawa; Arozatulo Bawamenewi; Miseri Cordias Palamarta Gulo; Fajar Iman Waruwu (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research investigates the factors influencing the use of Indonesian and regional languages among vocational high school students. Utilizing a qualitative research design and a case study approach, the study explores the impact of regional languages on students' use of Indonesian during daily school interactions. Data were gathered through observations and interviews with students, which were then subjected to a detailed case study analysis. The findings indicate that students often code-switch between Indonesian and regional languages during the learning process. While regional languages are predominantly used in peer interactions for better mutual understanding, Indonesian is more frequently employed in teacher-student interactions, particularly when answering questions. Despite teachers' efforts to promote the use of Indonesian, regional languages persist in informal settings. This study underscores the dynamic relationship between regional languages and Indonesian, highlighting the necessity for language policies that support multilingualism within educational settings